Structure of the flow in the inter-tube channel of the nozzle apparatus with a rotary diaphragm - Александр Григорьевич Жирков (National Aerospace University «Kharkiv Aviation Institute», 2021)
In the process of developing a numerical study method of a flat flow around a snap line with a rotary diaphragm, calculations were made at various degrees of opening the rotary diaphragm δ and pressure drops on the grille. As a result of calculations, for small degrees, the opening of the rotary diaphragm, complex patterns of the flow were obtained, in the inter-tube channel of the nozzle apparatus. The article presents some results of a numerical study of the supersonic flow in the channel of the nozzle apparatus with the degree of opening the rotary diaphragm δ = (0.15 ÷ 0.3). Modeling and calculating the flow of the working fluid is made using the Fluent software package. The construction of the calculated areas bounded by one inter-tube channel, for varying degrees of opening the diaphragm of the nozzle apparatus. Grids are built for calculated areas. Calculations were carried out for δ = (0.15 ÷ 0.3) and with different degrees of pressure drop on the grille. As a result of the calculations performed, the flow patterns in the inter-tube canal were obtained and behind it, and the distribution of the coefficients of the kinetic energy loss on the lattice front at various degrees of the discovery of the diaphragm at the inlet in the nozzle apparatus. According to the results of the work carried out, the following conclusions can be drawn: the structure of the stream in the inter-tube channel, the nozzle apparatus at small detection of the discovery, is divided into two parts: a supersonic core of the spawth of the blade and a dialing, the vortex zone at the back of the blade; The supersonic thread kernel at certain values of the relative pressure drop on the lattice (or the air flow values through the grid) is separated by shock fronts into several areas; The coefficients of energy loss, for small degrees of discovery, decrease with a decrease in the relative pressure drops (with an increase in the rate of expiration of the flow from the nozzle lattice); The greatest contribution to the magnitude of the loss of kinetic energy is introduced by a vortex zone in the inter-tube channel, and not wave phenomena in the core of the flow; Optimization of the flow part of the nozzle apparatus must be carried out in order to reduce areas with vortex flow. The results obtained in this work will be used to develop a methodology for a numerical study of the spatial flow around the nozzle lattices with rotary diaphragms.